Model Matematika Efek Repellent dalam Penularan Demam Berdarah - Tegar Arifin Prasetyo (NUCLEUS, 2021)
Dengue is a disease that is a health problem in the tropics and subtropics. There are 4 serotypes of dengue virus, DEN1-DEN4 and all of these serotypes are transmitted through the bite of female Aedes Aegypty mosquitoes. The big concern of the world health experts is the possibility of spreading dengue and becoming an uncontrolled epidemic. So this research is intended to be able to suppress dengue cases. We used is SIR-SI by adding all human classes do not or use repellent. The analysis conducted basic reproductive numbers  which will be reviewed when R0<1  and R0>1 . Furthermore, to illustrate the model was carried out simulation which resulted in the fact that the higher the level of repellent use in humans would reduce the spread of dengue.